2016
DOI: 10.3389/fcimb.2016.00156
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Efficient Elimination of Vibrio cholerae with a Chemical Modulator that Targets Glucose Metabolism

Abstract: Vibrio cholerae, a Gram-negative bacterium, is the causative agent of pandemic cholera. Previous studies have shown that the survival of the seventh pandemic El Tor biotype V. cholerae strain N16961 requires production of acetoin in a glucose-rich environment. The production of acetoin, a neutral fermentation end-product, allows V. cholerae to metabolize glucose without a pH drop, which is mediated by the production of organic acid. This finding suggests that inhibition of acetoin fermentation can result in V.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This ion uptake is essential to replace the lost electrolytes and water caused by the voluminous diarrhea caused by cholera toxin (23). On the other hand, there are concerns that the glucose content in ORS might worsen the disease by increasing the expression of toxic genes in El Tor strains (22). Here we reversed the inductive effect of glucose on El Tor strains by using acid-producing E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ion uptake is essential to replace the lost electrolytes and water caused by the voluminous diarrhea caused by cholera toxin (23). On the other hand, there are concerns that the glucose content in ORS might worsen the disease by increasing the expression of toxic genes in El Tor strains (22). Here we reversed the inductive effect of glucose on El Tor strains by using acid-producing E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, acetoin production offers V. cholerae cells a survival advantage during infection by downregulating the host innate immune responses (21). Another report showed that inhibiting acetoin production could be an antibacterial mechanism for V. cholerae elimination (22). Previous work explored another way to reduce the growth of El Tor strains in vitro by using a coculture of E. coli that is acid producing in the presence of glucose in the medium (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial SR has been a target to be inhibited. Chemical compounds that can suppress (p)ppGpp production, such as relacin (74) and iMAC (75), can potentially be used as antibiotic adjuvants. We anticipate that experimental data provided in the current study will stimulate future investigations that eventually help us come up with better strategies to combat bacterial infections, including one by the deadly enteric pathogen V. cholerae.…”
Section: Stringent Response and Antibiotic Tolerance In V Choleraementioning
confidence: 99%
“…This change in V. cholerae population has remained a contradiction, of which a difference in glucose metabolism between the 2 biotype strains has been widely accepted to be a cause 5 . El Tor biotype strains use glucose by neutral fermentation, whereas classical biotype strains perform acidic fermentation of glucose, which is considered an advantage for the former with regard to survival in a host and perhaps in nature 5,6 .…”
mentioning
confidence: 99%